Certain Metabolic Syndrome Component Combinations are Linked to Increased Risk of Hypogonadism in Taiwanese Men - Hong YH; Hung KC; Lin CL; Hung CL; Tu SK; Yang DH; Liao CC (Diabetes, Metabolic Syndrome and Obesity, 2025)
Yu-Han Hong,1 Kuang-Chen Hung,2– 5 Chih-Li Lin,6 Chia-Lien Hung,7 Shih-Kai Tu,1 Deng-Ho Yang,5,7– 9 Chun-Cheng Liao1,5– 7 1Department of Family Medicine, Taichung Armed Forces General Hospital, Taichung, Taiwan; 2Department of Surgery, Kaohsiung Veterans General Hospital, Kaohsiung, Taiwan; 3School of Medicine, National Sun Yat-sen University, Kaohsiung, Taiwan; 4College of Health Sciences, Central Taiwan University of Science and Technology, Taichung, Taiwan; 5School of Medicine, National Defense Medical Center, Taipei, Taiwan; 6Institute of Medicine, Chung Shan Medical University, Taichung, Taiwan; 7Department of Medical Education and Research, Taichung Armed Forces General Hospital, Taichung, Taiwan; 8Department of Medical Laboratory Science and Biotechnology, Central Taiwan University of Science and Technology, Taichung, Taiwan; 9Division of Rheumatology/Immunology/Allergy, Department of Internal Medicine, Taichung Armed Forces General Hospital, Taichung, TaiwanCorrespondence: Chun-Cheng Liao, Family Medicine Department, Taichung Armed Forces General Hospital, 348, Sec. 2, Zhongshan Road, Taiping Dist, Taichung, 411228, Taiwan, Tel +886423934191#525239 ; +886970703499, Fax +88623934191, Email milkbottle97@yahoo.com.twPurpose: This study examined the association between specific combinations of metabolic syndrome (MS) components and the risk of hypogonadism in Taiwanese men.Patients and Methods: We retrospectively analyzed 6,986 men who underwent health screening from 2009 to 2017. MS was defined as meeting at least three of five criteria: waist circumference (W), triglycerides (T), high-density lipoprotein cholesterol (H), fasting glucose (F), and blood pressure (B). Hypogonadism was defined as total testosterone < 300 ng/dL. Differences in MS component prevalence between men with and without hypogonadism were compared. Logistic regression adjusted for age and body mass index was used to assess associations.Results: Among all participants, 6,221 (89.0%) had hypogonadism. The prevalence of MS components was significantly higher in this group (p < 0.001). The risk of hypogonadism increased with the number of MS compon ents. Notably, the combinations F-H-W, F-H-B-W, and F-T-H-B-W were associated with significantly higher odds of hypogonadism.Conclusion: Specific MS component combinations are strongly associated with increased hypogonadism risk in Taiwanese men. These findings suggest that MS composition, not just its presence, should be considered in evaluating testosterone deficiency.Keywords: metabolic syndrome, hypogonadism, blood pressure, fasting blood glucose, high-density lipoprotein